A Novel DNA Vaccine Coding For H5 and N1 Genes of Highly Pathogenic Avian Influenza H5N1 Subtype - Eman, MS Elnagar; Saad, MA; Maha, AN Gamal; Zaki, FF; Soliman, YA (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Control of avian influenza infection requires a good vaccine that could induce both humoral and cell-mediated immune response, specifically IFN-ɣ production, to maintain a high level of protection along with the minimal level of viral shedding after the infection to prevent secondary epidemics. In the current study, deoxyribonucleic Acid (DNA) vaccine coding for full-length H5 and N1 genes have been produced and evaluated in SPF-chicken. Humoral immune response estimated by haemagglutination inhibition (HI) assay revealed that the DNA vaccine gave a high titer of antibodies at the day 28-post vaccination and 14 days post-challenge. However, the shedding level was minimal with the DNA vaccine (0.1 Log 10 EID50). The IFN-ɣ transcript was upregulated at a higher level in the DNA vaccinated group. The results revealed that the DNA vaccine could induce a high level of humoral and IFN-ɣ level that maintains a high level of protection (92%) with the advantage of limiting the shedding level and thus, prevent secondary epidemics.